2023
DOI: 10.3390/futurepharmacol3040053
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Therapeutic Potential of Medicinal Plants for Alzheimer’s Disease: Preclinical to Clinical Trial Insights

Kushagra Nagori,
Kartik T. Nakhate,
Krishna Yadav
et al.

Abstract: Alzheimer’s disease (AD) is a progressive, multifactorial, and unremitting neurodegenerative disease characterized by memory loss, personality changes, and cognitive impairment. It has become more prevalent in recent years. Therefore, understanding the pathophysiology of AD and developing efficient therapeutic strategies are essential. Moreover, the progression of the disease is unaffected by the pharmaceutical approaches discovered to date. Additionally, the failure of over 200 potential drug candidates in cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 173 publications
0
3
0
Order By: Relevance
“…Therefore, the search for new approaches to AD therapy is crucial to address the growing burden of this pathology. Medicinal herbs are a promising avenue for the treatment of AD [ 228 , 229 , 230 , 231 , 232 , 233 ]. Natural compounds were the first therapy used for AD [ 233 ].…”
Section: Natural Compounds As a Novel Treatment For Admentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the search for new approaches to AD therapy is crucial to address the growing burden of this pathology. Medicinal herbs are a promising avenue for the treatment of AD [ 228 , 229 , 230 , 231 , 232 , 233 ]. Natural compounds were the first therapy used for AD [ 233 ].…”
Section: Natural Compounds As a Novel Treatment For Admentioning
confidence: 99%
“…Natural compounds were the first therapy used for AD [ 233 ]. Although the mechanisms of therapeutic effects of ayurvedic medicinal herbs remain largely unknown, extensive experimental and clinical studies on phytochemical actions have found a wide range of beneficial effects for AD within these plants [ 228 , 229 , 230 , 231 , 232 , 233 ]. There are several natural components exhibiting therapeutic effectiveness for AD, including flavonoids, polyphenols, sterols, alkaloids, triterpenes, lignans, and tannins with effects against to oxidative stress, neuroinflammation, amyloid deposition, and activity of cholinesterase.…”
Section: Natural Compounds As a Novel Treatment For Admentioning
confidence: 99%
“…Plant-derived sources present an alternative reservoir of bioactive compounds with potential applications of therapeutic or prophylactic agents against various diseases [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. To date, 350,000 vascular plant species are known, and new species are discovered yearly [ 16 ].…”
Section: Introductionmentioning
confidence: 99%